Hainaz Clean / Khairul Anuar Ahmad - Ahmad, Khairul Anuar (2020)
Hainaz Clean was designed to penetrate small medium consumer market through online purchase and marketing. On top of that, we also target small grocery store and supermarket to increase our sales. Hainaz Clean have appointed agent to deliver our product to the consumer. Online sales will be delivered by using courier services while our cash sales are through our agent. We have variety of product focusing on the cleaning detergent. As of now, we have laundry detergent, handwash detergent, fabric softener, and body shower.